Factors Associated with Safety Behavior among Basic Professional Practices of Vocational Students in Thailand - ชำนาญเวช, พงษ์ดนัย; แก้วบุญชู, อรวรรณ; บุณยมาลิก, เพลินพิศ (Journal of The Royal Thai Army Nurses, 2019)
This study aims to examine safety behavior among basic professional practices of vocational students and factors associated with safety behavior among basic professional practices. The subjects were 420 diploma vocational students affiliated with the office of vocational education commission. The research questionnaire consists of 5 parts: 1) demographic variables 2) safety climate 3) safety knowledge 4) safety motivation and 5) safety behavior. The data were analyzed by descriptive statistics and spearman rank correlation. The results revealed that safety behavior among basic professional practices of vocational students were at a high level (Mean = 30.05, SD = 4.81). Factors associated with safety behavior among basic professional practices were safety climate (r = .49, p < .05), safety knowledge (r = .37, p < .05) and safety motivation (r = 0.49, p < .05) and factors disassociated with safety behavior among basic professional practices were gender (r = 0.02, p = .56) age (r = -.02, p = .62) years of education (r = -.04, p = .41) practice or classroom lesson in occupational health and safety subjects before basic professional practices (r = .02, p = .55), and past illness/injury experience from basic professional practices. (r = .03, p-value = .52)